Elevated Serum PSA is Associated With Human Herpesvirus 8 Infection and Increased Circulating Cytokine Levels in Men From Tobago. Issue 6 (24th January 2017) - Henning, Jill D.; Karamchandani, Jaideep M.; Bonachea, Luis A.; Bunker, Clareann H.; Patrick, Alan L.; Jenkins, Frank J.
Abstract : BACKGROUND: Serum‐prostate specific antigen (PSA) levels have been used for many years as a biomarker for prostate cancer. This usage is under scrutiny due to the fact that elevated PSA levels can be caused by other conditions such as benign prostatic hyperplasia and infections of or injury to the prostate. As a result, the identification of specific pathogens capable of increasing serum levels of PSA is important. A potential candidate responsible for elevated PSA is human herpesvirus 8 (HHV‐8). We have reported previously that HHV‐8 is capable of infecting and establishing a latent infection in the prostate. In this current study we test the hypothesis that HHV‐8 infection is associated with elevated PSA levels. Circulating cytokine levels between men with elevated PSA and controls are also compared. METHODS: HHV‐8 serostatus was determined among men with elevated serum PSA (≥4 ng/ml; n = 168, no prostate cancer on biopsy) and age‐matched controls (PSA <4 ng/ml; n = 234), Circulating cytokine levels were determined among a subset of each group (116 with elevated PSA and 85 controls). RESULTS: Men with an elevated serum PSA were significantly more likely to be HHV‐8 seropositive (42.9%) than the age‐matched cancer‐free men (22.2%; OR 2.51; 95%CI 1.48–4.29, P  = 00001). Comparison of circulating cytokine levels between men with elevated serum PSA and controls indicated that elevated serum PSA is associated with a pro‐inflammatory response with a mixed Th1/Th2 response while HHV‐8 infection was associated with significantly higher levels of IL12p70, IL‐10, and IL‐13 indicating a Th2 immune response. CONCLUSIONS: We found a significant association between HHV‐8 infection and increased levels of serum PSA. In an age of patient‐centered medicine, men with an elevated serum PSA should be considered for HHV‐8 serology testing to determine if HHV‐8 is responsible for the elevated PSA. Prostate 77: 617–624, 2017 . © 2017 Wiley Periodicals, Inc.